PEMBATALAN PERNIKAHAN KARENA HOMOSEKSUAL: Studi Analisis Putusan Pengadilan Agama Jember No. 44/Pdt.G/2023/PA.Jr - Rustam, Muhammad Yusup; Kumaini, Ruston; Ramadhan, Abdul Rahman (Al-Majaalis : Jurnal Dirasat Islamiyah, 2025)
Marriage is a bond that is expected to be harmonious. However, there are several conditions that can undermine this goal, one of which is dishonesty about sexual orientation before marriage. This can be a significant factor that undermines trust and disrupts the rights of partners in achieving the goals of their marriage. This research analyses the annulment of marriage due to sexual orientation in Jember Religious Court Decision No. 44/Pdt.G/2023/PA.Jr. This case involved a wife who applied for marriage cancellation after discovering that her husband was homosexual, who only disclosed it after the marriage took place. Based on Marriage Law No. 1 of 1974 and the Compilation of Islamic Law (KHI), marriage cancellation can be filed if there is an element of deception or misrepresentation regarding the identity of the spouse. This research aims to explore two legal perspectives on the cancellation of this marriage, namely Indonesian positive law and Islamic law. A qualitative approach was used with a literature study method to analyse this decision. The results of this study show that the Jember Religious Court Decision No. 44/Pdt.G/2023/PA.Jr cancelled the marriage due to deception regarding the sexual orientation of the couple, in accordance with Article 27 of the Marriage Law and Article 72 of KHI. The marriage was declared legally invalid to protect the applicant's right to justice. Fasakh in Islamic law is the cancellation of a valid marriage if a defect or disgrace is found that violates the conditions of marriage, such as homosexuality, as decided in case No. 44/Pdt.G/2023/PA.Jr.